A short-term perceptual priming account of spacing effects in explicit cued-memory tasks for unfamiliar stimuli - Mammarella, Nicola; Avons, S. E.; Russo, Riccardo (European journal of cognitive psychology, 2004)
Memory for repeated items improves when presentations are spaced during study. This effect is found in explicit memory tasks using different types of material, different experimental paradigms, and in different subject populations. Two experiments are described where the spacing effect was assessed on a yes/no recognition memory task using words and nonwords as targets. The main results showed that changing the font between repeated occurrences of targets at study did not affect the spacing effect for words, even under shallow encoding conditions, but effectively removed the spacing effect with nonwords. In both experiments, the font manipulation was made between subjects, ruling out explanations in terms of differential attention to particular font conditions. These results provide further support for short-term perceptual priming accounts of the spacing effect: Semantically-based repetition priming affects memory for words; perceptual priming mechanisms affect memory for nonwords.